Pengaruh Dukungan Keluarga Terhadap Pendidikan Karakter Mahasiswa - Defa Andini Fadillah; Pinkan Yustisya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The importance of character education in developing students' personalities is the background of this study. Family support is a major variable that influences character education. Strong family values ​​are considered to strengthen the good character qualities that students learn during school. The purpose of this study was to examine the effect of family support on students' character education. This study used a quantitative survey-based methodology. A questionnaire was used to collect data from 102 students. Supporting papers and literature were found by searching for scientific articles in scientific databases such as Publish or Perish and Google Scholar. The findings of the study indicate a strong and beneficial influence between students' character education and family support. This suggests that students' character development is positively correlated with family support.